Effect of sugar positions in ginsenosides and their inhibitory potency on Na+/K+-ATPase activity - Chen Ronald JY; Chung Tse-yu; Li Feng-yin; Lin Nan-hei; Tzen Jason TC (Acta Pharmacologica Sinica, 2016)
Aim: To determine whether ginsenosides with various sugar attachments may act as active components responsible for the cardiac therapeutic effects of ginseng and sanqi (the roots of Panax ginseng and Panax notoginseng) via the same molecular mechanism triggered by cardiac glycosides, such as ouabain and digoxin. Methods: The structural similarity between ginsenosides and ouabain was analyzed. The inhibitory potency of ginsenosides and ouabain on Na+/K+-ATPase activity was examined and compared. Molecular modeling was exhibited for the docking of ginsenosides to Na+/K+-ATPase. Results: Ginsenosides with sugar moieties attached only to the C-3 position of the steroid-like structure, equivalent to the sugar position in cardiac glycosides, and possessed inhibitory potency on Na+/K+-ATPase activity. However, their inhibitory potency was significantly reduced or completely abolished when a monosaccharide was linked to the C-6 or C-20 position of the steroid-like structure; replacement of the monosaccharide with a disaccharide molecule at either of these positions caused the disappearance of the inhibitory potency. Molecular modeling and docking confirmed that the difference in Na+/K+-ATPase inhibitory potency among ginsenosides was due to the steric hindrance of sugar attachment at the C-6 and C-20 positions of the steroid-like structure. Conclusion: The cardiac therapeutic effects of ginseng and sanqi should be at least partly attributed to the effective inhibition of Na+/K+-ATPase by their metabolized ginsenosides with sugar moieties attached only to the C-3 position of the steroid-like structure.